Enhancing Students’ Literacy Through Intellectual Diary: A Classroom Approach - Muh. Hasbi; Fitriyani Bakri; Abdul Halim (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
In higher education context, many students encounter considerable difficulties in improving their literacy skills, which limits their ability to fully engage with course material and reach their academic potential. This study aims to explore how the use of intellectual diaries have significant influence in enhancing the literacy skills of university students enrolled in an English prose course. This study employed a qualitative research design with a case study approach focusing on in-depth examination of a single class of students in their natural classroom setting. The participants in this study were 34 undergraduate students enrolled in an English prose course at a state university located in Makassar city, Indonesia. Data were collected through three primary instruments: intellectual diaries, semi-structured interviews, and classroom observations. Data analysis was conducted using thematic analysis with six steps implementation stages. The findings revealed four key themes in dealing with students’ intellectual diary: enhanced critical thinking, improved reading comprehension and analytical abilities, increased self-reflection and metacognitive awareness, and greater engagement with course material. These findings suggest that intellectual diaries can be a valuable tool for promoting literacy development in higher education. The study's findings contribute to the existing body of knowledge on literacy education by providing empirical evidence of the benefits of intellectual diaries in an English prose course context.